RANCANG BANGUN PENDETEKSI MOBIL PADA LAHAN PARKIR MENGGUNAKAN MOTION DETECTION - Wibawa, Isana Mahardika Laksana; Harianto, Harianto; Wibowo, Madha Christian (Journal of Control and Network Systems (JCONES), 2016)
Abstract: many riders got into trouble when it wants to find an empty parking space. in addition to the vast area alternating riders also have to see where the parking area is empty, it is waste of time and not efficiencythe current system is used to detect an empty parking lot is by installing a sensor object., within each slot, the shortcomings of the system are all objects that were in the car when the slot is in the sensor reach it is considered a car and the system requires a lot of money. it made system using existing cameras can create a system that can detect an empty parking area using background subtraction and supported by motion detection. where the camera will take a picture of the parking conditions are then sent to the PC. After which it will be processed by the system which will detect an empty parking space and then the results will be shown the places where only the slot is empty. in this system has conducted 155 trials with a minimum percentage of 35% white pixels that have been obtained from several experiments for accurate results.Keywords : parking, image, camera, motion detection background subtraction method